Alcohol Use Disorders in ICD‐11: Past, Present, and Future. (23rd July 2019) - Saunders, John B.; Degenhardt, Louisa; Reed, Geoffrey M.; Poznyak, Vladimir
Abstract : The Eleventh Revision of the International Classification of Diseases (ICD‐11) was formally published in May 2019. Alcohol use disorders form a key part of the section of Disorders due to Substance Use and Addictive Behaviours. This review describes and discusses the alcohol diagnoses within this section of ICD‐11, including Alcohol Dependence, Harmful Pattern of Use of Alcohol, and entities such as Alcohol Intoxication, Alcohol Withdrawal, and several alcohol‐induced mental disorders, and briefly covers Hazardous Alcohol Use, which is listed separately as a health risk factor. We summarize the historical background to the development of these diagnoses, including work within the World Health Organization since the 1970s, and the corresponding diagnoses in the current ICD‐10. The process by which ICD‐11 diagnoses have been made is described and may be summarized as a conceptual–pragmatic–confirmatory one. The available empirical data supporting the ICD‐11 diagnoses are presented, particularly in relation to the diagnostic guidelines for Alcohol Dependence. Comparison is made with the corresponding diagnoses in ICD‐10 and their nearest counterparts in the fourth and fifth editions of the Diagnostic and Statistical Manual of Mental Disorders. Field testing of the ICD‐11 diagnoses is currently in progress. A plea is made for matching of diagnoses, diagnostic guidelines/criteria, and the assessment tools intended to capture these diagnoses. Abstract : In ICD‐11 the diagnosis of Alcohol Dependence has been retained, in simplified format, as the central alcohol use disorder. Concordance with its ICD‐10 and DSM‐IV equivalents is excellent, but it does not tally well with the broadly formulated DSM‐5 Alcohol Use Disorder. Work is needed to develop the most effective crosswalk between the two. ICD‐11 Harmful Alcohol Use is a non‐dependence disorder; it signifies repeated alcohol consumption which has caused harm or through the person's behaviour, harm to others.